Enchanting Math AudibleBook: Insights from Teachers, University Students, and Young Learners - Alim, Jesi Alexander; Oktaviani, Cici; Hermita, Neni; Putra, Zetra Hainul (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2023)
Reading is an essential activity of learning. In this study, the researchers investigated the opinions of elementary school teachers, university students majoring in elementary school teacher education, and elementary school students on the mathematics audible book "Asyiknya Bermain Setatak". The researchers distributed questionnaires to collect the data. Data collection was carried out randomly using the random sample method. The respondents comprised 75 people (9 elementary school teachers, 53 university students majoring in elementary school teacher education, and 13 elementary school students) in Pekanbaru, Riau. The data were analyzed using  Rasch Model with item response theory (IRT). Based on the data analysis, all statements are valid and reliable, and it means that the items can be used to judge the design of the audible book "Asyiknya Bermain Setatak".Based on the results of the study, it was found that the audible book math media was in accordance with the learning of elementary school students. The use of math audible book is also easy to do by students, teachers, and prospective teachers. Math audible books also provide positive benefits in learning mathematics. Based on this, it can be concluded that teachers should consider using audible books as a media for mathematics learning.